2013
DOI: 10.5847/wjem.j.issn.1920-8642.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell injury with inflammatory cytokine and coagulation in patients with sepsis

Abstract: BACKGROUND: Current studies on CD62P have focused mainly on cardiovascular diseases, while only few studies have evaluated the effects of CD62P on the development of sepsis and the association between endothelial cell injury with infl ammation and coagulation. This study attended to explore the association between endothelial cell injury with infl ammation and coagulation by evaluating the expression of soluble CD62P (s-CD62P) in plasma and its mechanism in patients with sepsis, thus to provide the evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
10
2
Order By: Relevance
“…[27][28][29][30] Activated PTT is also known to be prolonged in severe systemic inflammatory response syndrome complicated by thrombotic coagulopathy. 31,32 In our study, no significant correlation was observed between aPTT and inflammatory indices. The fact that ACT is influenced by more variables Abbreviations: ACT, activated clotting time; aPTT, activated partial thromboplastin time; CRP, C-reactive protein; INR, international normalized ratio; NEU, neutrophil count; PLT, platelet count; WBC, white blood cell count.…”
Section: Discussioncontrasting
confidence: 66%
“…[27][28][29][30] Activated PTT is also known to be prolonged in severe systemic inflammatory response syndrome complicated by thrombotic coagulopathy. 31,32 In our study, no significant correlation was observed between aPTT and inflammatory indices. The fact that ACT is influenced by more variables Abbreviations: ACT, activated clotting time; aPTT, activated partial thromboplastin time; CRP, C-reactive protein; INR, international normalized ratio; NEU, neutrophil count; PLT, platelet count; WBC, white blood cell count.…”
Section: Discussioncontrasting
confidence: 66%
“…Moreover, CCB has been shown lower oxidative burst and inducible nitric oxide synthase (iNOS) protein expression to regulate in ammatory response (38), and ameliorates cellular injury and cardiac dysfunction. Most importantly, sepsis disrupts intracellular calcium homeostasis which lead to endothelial injury and destroyed subcelluar structures (39,40). CCB, which is involved in targeting and blocking calcium ions overload (41,42), can reduce intracellular Ca 2+ levels and prevent cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Reaction of D-dimer coagulation and platelets between the two groups showed a signifi cant difference on day 7, but not day 1, suggesting supplemental values of these indicators for prognosis in sepsis. [19][20][21] These changes in PCT, endotoxins, D-dimer coagulation and platelets are useful indicators in monitoring progress of sepsis and provide guidance for timely treatment.…”
Section: Discussionmentioning
confidence: 99%